Soil nail and guniting works in Pahang / Damanhuri Jamalludin … [et al.] - Jamalludin, Damanhuri; Ahmad, Mohd Farid; Ibrahim, Anas (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
Repair works for road embankment failure using soil nail and guniting are presented. The road failures occurred along Genting Highlands to Bukit Cincin Road, Pahang, Malaysia. It links the Genting Highlands town and the Department of Civil Aviation Radar station, which is situated at Bukit Cincin. The total length of this hilly and winding road is about 2.0 km and is 3.5 m wide. It was constructed in 1975. A total of 10 embankment failures occurred along the road on 30th October 1997 during the rainy seasons. Only repair works at Location 10 using soil nails and guniting are fully explained. The embankment stability was improved using soil nails while gunite was used to prevent embankment surface erosion.